Synthesis of MgNiCo LDH hollow structure derived from ZIF-67 as superb adsorbent for Congo red - Wang, Xing; Cheng, Bei; Zhang, Liuyang; Yu, Jiaguo; Li, Youji (Journal of colloid and interface science, 2022)
[Display omitted] •Polyhedron MNC HS was synthesized using ZIF-67 as template.•It has a porous structure and large specific surface area.•It showed excellent adsorption capacity and good recovery for Congo red.•It can be as a promising candidate for removal of CR pollutants. Adsorption materials with large specific surface area and porous structures exert a beneficial impact on improving the adsorption performance. In this work, MgNiCo LDH hollow structure (MNC HS) is fabricated through a simple one-step solvothermal method using ZIF-67 as the sacrificial template. Electron microscopy shows that the MNC HS retains the dodecahedral shape of ZIF-67. The as-prepared sample exhibits efficient adsorption for Congo red (CR) in water, which is due to the hierarchical structure and large specific surface area that provides more adsorption sites and electrostatic interaction. The CR adsorption process fits the pseudo-second-order model better by kinetics simulation; while Langmuir model is more accurate than Freundlich model in describing the adsorption isotherms of CR. The maximum adsorption capacity calculated by the Langmuir model can reach 1194.7 mg g−1, which is much higher than that of the sample MgNiCo LDH (MNC) synthesized by conventional methods. The cycle tests also show that the as-prepared adsorbent has good stability and recycling ability.